Girl, stolen - Henry, April (Henry Holt, 2010)
When an impulsive carjacking turns into a kidnapping, Griffin, a high school dropout, finds himself more in sympathy with his wealthy, blind victim, sixteen-year-old Cheyenne, than with his greedy father.